Circadian rhythm in gastrointestinal cancer: clinical applications and future perspectives - Jinxin Han; Zhen Xiong; Yang Liu; Jialiang Li; Chao Li; Weikang Zhang; Jinbo Gao; Xiaoming Shuai; Zheng Wang; Guobin Wang; Xiaogang Shu; Kaixiong Tao; et al. (Annals of Medicine)
Gastrointestinal cancer (GIC) ranks among the most fatal malignancies globally and is characterized by a significant propensity for metastasis. While surgical intervention can effectively cure GIC in its early stages, a substantial number of cases are diagnosed at advanced stages, where the response to current therapeutic options is markedly diminished. Increasing evidence highlights the pivotal role of circadian rhythm, an intrinsic 24-hour cyclical system regulating biological activities to adapt to the alternations of day and night in the progression, metastasis, and development of chemoresistance in GIC. Recent studies have disclosed that the modulation of key circadian rhythm genes (such as BMAL1 and PER1) can suppress tumor advancement through multiple pathways. This review compiles the most recent research concerning the circadian rhythm and its influence on GIC progression. It elucidates the role of circadian genes in the initiation, metastasis, metabolism, inflammatory response, and therapeutic resistance in GIC, including both chemotherapy and targeted therapies. Furthermore, the review discusses the current implementation and future outlook of therapeutic strategies based on circadian modulation in the treatment of GIC.